Little Difference in Milk Fatty Acid and Terpene Composition Among Three Contrasting Dairy Breeds When Grazing a Biodiverse Mountain Pasture - Koczura, Madeline; Martin, Bruno; Musci, Marilena; Massimo, Martina Di; Bouchon, Matthieu; Turille, Germano; Kreuzer, Michael; Berard, Joel; Coppa, Mauro (Frontiers in Veterinary Science, 2021)
In the mountains, autochthonous and robust breeds are often used to valorize biodiverse grasslands. Along with their lower nutrient requirements, compared to specialized dairy breeds, they are expected to be better adapted to complex environments and valorize grasslands into dairy products of high quality. Therefore, the aim of the present study was to investigate the grazing selection of three contrasting dairy breeds on a biodiverse mountain pasture, and its consequences on milk fatty acid (FA) profile and prevalence of individual terpenes. A dual-purpose breed from the Italian Alps, the Valdostana Red Pied (Va), was compared to Montbéliardes (Mo), more specialized in milk production, and the highly specialized Holsteins (Ho). Diet selection was measured by scan-sampling, calculating selectivity indexes, and collecting simulated bites during two consecutive days in June (end of first grazing cycle) and July (second grazing cycle). Milk samples were collected at each milking during these experimental periods. Yield of milk and its fat and protein contents were measured. Milk FA and terpenes were analyzed by gas chromatographic methods. We tested the effects of breed, period and their interaction in a repeated mixed model, and calculated Pearson’s correlations between behavioral data and milk FA as well as terpenes. The Va grazed less mature vegetation than Ho, but this difference was not sufficient to lead to a major breed effect on milk FA profile and prevalence of terpenes. However, the proportion of α-linolenic acid (C18:3 n-3) was always higher in the milk fat of Va than Ho (Mo were intermediary), but this without any correlation to grazing selection. This could be a consequence from a different metabolism concerning ruminal biohydrogenation, but must be further investigated. Finally, we confirmed previous studies that highlighted a link between milk quality and cows’ grazing behavior, but here without differences among breeds. All cows adapted their behavior to the herbage evolution during the season, leading to higher proportions of unsaturated FA in July than June milks. Our study suggests that under mountain grazing conditions (biodiverse pasture and cows in late lactation), milk quality depends more on herbage composition than on cow breed.